From the body to the psyche: An observational study about hospitali - Lo Cascio, Gelsomina; Cozzolino, Raffaella; Giordano, Antonio; Silvestri, Nicola; Maiorino, Cosimo; Vito, Alberto (Quaderni di Psicologia Clinica, 2014)
Hospitalization is a critical event that significantly influences the quality of life, because it represents a great source of stress, as physical as mental. The purpose of this observational study was to evaluate the perception of hospitalization's experience in patients admitted to "Azienda Ospedaliera di Rilievo Nazionale dei Colli – Ospedale CTO”, Naples. Our results show the importance of health care not only from a physical point of view healing organic disease, but also by an psychological approach.
Keywords: psychological support; stress; satisfaction; hospitalization; somatization